Density functional theory investigation of the mechanical, electronic and optical properties of Pb-free vacancy-ordered double perovskites K2PdCl6 and K2PdBr6. (10th January 2022) - Zhao, Xian-Hao; Tang, Tian-Yu; Xie, Quan; Lu, Li-Min; Tang, Yan-Lin
Abstract: The current work has investigated the mechanical, electronic and optical properties of Pb-free vacancy-ordered double perovskites K2 PdCl6 and K2 PdBr6 by using first-principles calculations based on the framework of density functional theory (DFT). The calculated lattice constants of K2 PdCl6 and K2 PdBr6 are close to the experimental data. It is determined by calculating the Goldschmidt's tolerance factors and elastic constants of K2 PdCl6 and K2 PdBr6 that they can be stabilized into 3D cubic crystal structures. The calculated Poisson and Pugh's ratios indicate that K2 PdCl6 is a brittle material, while K2 PdBr6 exhibits ductile behavior. Both K2 PdCl6 and K2 PdBr6 are indirect band gap semiconductors, which show suitable band gaps of 2.151 eV and 1.368 eV for optoelectronic devices, respectively. In addition, the optical properties of K2 PdCl6 and K2 PdBr6 in the photon energy range of 0–6 eV further reveal the application potential of these compounds in single-junction and tandem solar cells as well as other optoelectronic devices.